1999
DOI: 10.1038/sj.bjp.0702442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α‐trinositol on interstitial fluid pressure, oedema generation and albumin extravasation in experimental frostbite in the rat

Abstract: 1 The anti-in¯ammatory eect of a-trinositol (D-myo-inositol-1,2,6-trisphosphate) on oedema formation, microvascular protein leakage and interstitial¯uid pressure (P if ) in rat skin after frostbite injury, was investigated. a-Trinositol (40 mg kg body weight 71 ) was administered intravenously as a bolus both before and/or in the interval between freezing and thawing of the tissue. 2 P if was measured in rat paw skin with micropipettes connected to a servo-controlled counterpressure system. Oedema formation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Later experiments suggested that the P if reduction was associated with denaturation of collagen (276) and introduced the concept that the interstitium can "actively" contribute in P if regulation and thus enhance rather than prevent filtration. Such a mechanism of edema generation has later been confirmed in other burn injury models (245,428) and in frostbite injury (46). Although less pronounced, inflammation induced by a multitude of agents without simultaneous denaturation of collagen also resulted in P if reduction (for references, see Ref.…”
Section: Interstitial Pressure and Flow In Inflammation And Injurymentioning
confidence: 61%
See 3 more Smart Citations
“…Later experiments suggested that the P if reduction was associated with denaturation of collagen (276) and introduced the concept that the interstitium can "actively" contribute in P if regulation and thus enhance rather than prevent filtration. Such a mechanism of edema generation has later been confirmed in other burn injury models (245,428) and in frostbite injury (46). Although less pronounced, inflammation induced by a multitude of agents without simultaneous denaturation of collagen also resulted in P if reduction (for references, see Ref.…”
Section: Interstitial Pressure and Flow In Inflammation And Injurymentioning
confidence: 61%
“…In rats, P i rose by 2 mmHg to approximately ϩ1 mmHg, and the compliance in hindlimb skin was almost infinite at a hydration 2-3 times control (504). In freeze injury, however, the volume-pressure relationship in rat paw skin was linear up to an overhydration of 140% with a corresponding C i of 6%/mmHg (46). A C i more than 50% lower than in dehydration in normal rats (504) suggests that the matrix is stiffer in this injury model, an assumption supported by the dramatic increase in P if that rose to 22 mmHg 60 min postfreeze (46).…”
Section: Compliance Of Normal Tissuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence from 1 LOE 3 bench study 276 demonstrated elevated levels of inflammatory mediators in blister fluid of frostbite patients. In 6 LOE 5 animal studies, 264,[277][278][279][280][281] frostbite treatment that included administration of a nonsteroidal anti-inflammatory drug (NSAID) either before or following injury was beneficial. Two LOE 4 case series 273,282 reported healing without major tissue loss when an NSAID was included in treatment protocols, while 2 LOE 4 studies 271,283 did not clearly describe outcomes.…”
Section: Fa-902bmentioning
confidence: 99%